2016
DOI: 10.7717/peerj.2445
|View full text |Cite
|
Sign up to set email alerts
|

Lithocholic acid induces endoplasmic reticulum stress, autophagy and mitochondrial dysfunction in human prostate cancer cells

Abstract: Lithocholic acid (LCA) is a secondary bile acid that is selectively toxic to human neuroblastoma, breast and prostate cancer cells, whilst sparing normal cells. We previously reported that LCA inhibited cell viability and proliferation and induced apoptosis and necrosis of androgen-dependent LNCaP and androgen-independent PC-3 human prostate cancer cells. In the present study, we investigated the roles of endoplasmic reticulum (ER) stress, autophagy and mitochondrial dysfunction in the toxicity of LCA in PC-3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 39 publications
2
42
0
Order By: Relevance
“…Previous studies have suggested the endoplasmic reticulum stress could determine apoptosis and cell death in cancers [37,38]. SSR1, regulated by miR-4521, was associated with the pathway of protein processing.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested the endoplasmic reticulum stress could determine apoptosis and cell death in cancers [37,38]. SSR1, regulated by miR-4521, was associated with the pathway of protein processing.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we identified a novel bacterial metabolite, IS, that possesses cytostatic features in breast cancer, similar to the short-chain fatty acids [ 61 , 62 ], lithocholic acid [ 16 , 45 , 50 , 78 , 79 , 80 , 81 ], cadaverine [ 17 , 51 ], and indole propionic acid [ 40 ]. Despite the conflicting results, the majority of breast cancer microbiome studies show suppressed diversity and biosynthetic capacity in breast cancer-associated oncobiosis [ 1 , 2 , 3 , 4 , 5 , 8 , 9 , 12 , 13 , 14 , 15 , 48 ], leading to limited biosynthetic capacity that lowers the level of protective bacterial metabolites in patients [ 16 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…IS administration reduces cell proliferation, infiltration into the surrounding tissues, and metastasis formation in cellular and animal models. This feature is a common trait for other cytostatic metabolites in breast cancer [ 16 , 17 , 40 , 45 , 50 , 51 , 61 , 62 , 78 , 79 , 80 , 81 ]. At the same time, IS did not affect non-transformed cells, again a common trait for bacterial cytostatic metabolites in breast cancer [ 16 , 17 , 40 , 78 ], suggesting that these metabolites have tumor cell-specific effects.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, autophagy and anoikis resistance induced by AEG‐1 were inhibited by siRNA against ATF4. Studies have shown that ER stress is strongly associated with autophagy in cancers (Cerezo & Rocchi, ; Gafar et al, ; Williams, Hou, Ni, & Ding, ). However, to our knowledge, it has not been reported before that ER stress may play a role in protective autophagy induced by AEG‐1.…”
Section: Discussionmentioning
confidence: 99%